“Operating Room Effectiveness”: Phenomenological Qualitative Study In Hospital - Teguh Tirto Katon; Sri Wahyuni Nasution; Tri Suci (International Journal of Health and Pharmaceutical (IJHP), 2023)
This study investigates the experience of health and medical personnel in hospital operating rooms and to evaluate the effectiveness of activities in operating rooms and ventilation conditions in hospitals. This study was designed as a qualitative research based on Heidegger's Hermeneutic Phenomenology Approach. The research method was carried out on health and medical personnel working in the operating room (OR) as observers. The research data were collected using an open and unstructured interview form. This form includes items that question the operating room design and operating room ventilation conditions. Data analysis used the Miles & Huberman method with the stages of data reduction, data display, and conclusion or verification. The research findings were obtained from seven informants (health and medical personnel) consisting of three men and four women. Age ranged from 30 to 45 years. Two themes and twelve sub-themes were determined as a result of data analysis. The research themes are (1) the effectiveness of operating room layout and (2) the effectiveness of operating room ventilation. This study concludes and provides important information about the physical requirements of the hospital operating room and the effectiveness for working professionally experience workers in the operating room (OR). It is understood that the room layout in the hospital is very good in helping smooth preoperative and postoperative handling. And operating room ventilation already supports good air circulation and is easy to control its use. But still found another room that causes noise. Hospital management must consider the type of activity, use of equipment, and/or other sources of noise, whether in the operating room building, ventilation of the operating room without a positive pressure system. So, the hospital must be able to pay attention to air humidity and pay attention to the state of the ventilation system and air filtration in the operating room so as to reduce the risk of preoperative and postoperative wound infections.